Quantitative determination of selected nutrients in lablab (Benthic Mat). - Remada, Riah Yutis
This study assessed lablab (Benthic mat), one of the natural feeds of many aquatic animals, as a potential feed ingredient. Results on proximate analysis are as follows. Lablab reveals its high nutritive value and digestibility because of its low crude fiber content (0.12 percent). Crude fat is significantly high (6.10 percent). Crude protein content is minimal (5.81 percent). Ash content is very high (79.05 percent) due to the presence of minerals that are utilizable by diatoms and othe phytoplankton., Determiantion of selected dietary minerals in Lablab was done to further assess lablab as a mineral source. Zinc was analyzed using Atomic Absorption Spectrophotometer. Lablab contains 66.63 ppm Zn. Iron and phospohorus analyses were done using Genysis UV-Vis Spectrophotometer. Fe content is very high (36, 390 ppm). Lablab contains 2,037 - ppm phosphorus (expressed as phosphate). Calcium was analyzed using Complexometric titration usng EDTA. Ca content is 1, 155 ppm. Lablab contians appreciable amount of iodine (2, 795 ppm). Iodine analysis was done using Elmslie-Caldwell Method.